The Use of Antiepileptic Drugs (AEDs) for the Treatment of Pediatric Aggression and Mood Disorders - Joseph Gonzalez-Heydrich; Peter Ducharme; Tanya Oken; Danielle J. Guild; Harsh K. Trivedi; Betty C. Wang; Kaizad R. Munshi (MDPI AG, 2010)
Aggressive symptomatology presents across multiple psychiatric, developmental, neurological and behavioral disorders, complicating the diagnosis and treatment of the underlying pathology. Anti-Epileptic Drugs (AEDs) have become an appealing alternative in the treatment of aggression, mood lability and impulsivity in adult and pediatric populations, although few controlled trials have explored their efficacy in treating pediatric populations. This review of the literature synthesizes the available data on ten AEDs - valproate, carbamazepine, oxcarbazepine, phenytoin, lamotrigine, topiramate, levetiracetam, zonisamide, gabapentin and tiagabine - in an attempt to assess evidence for the efficacy of AEDs in the treatment of aggression in pediatric populations. Our review revealed modest evidence that some of the AEDs produced improvement in pediatric aggression, but controlled trials in pediatric bipolar disorder have not been promising. Valproate is the best supported AED for aggression and should be considered as a first line of treatment. When monotherapy is insufficient, combining an AED with either lithium or an atypical anti-psychotic can result in better efficacy. Additionally, our review indicates that medications with predominately GABA-ergic mechanisms of action are not effective in treating aggression, and medications which decrease glutaminergic transmission tended to have more cognitive adverse effects. Agents with multiple mechanisms of action may be more effective.